Estimating the health consequences of flight attendant work: comparing flight attendant health to the general population in a cross-sectional study - Eileen McNeely; Irina Mordukhovich; Samuel Tideman; Sara Gale; Brent Coull (BMC, 2018)
Abstract Background Flight attendants are an understudied occupational group, despite undergoing a wide and unique range of adverse job-related exposures. In our study, we aimed to characterize the health profile of cabin crew relative to the U.S. general population. Methods In 2014-2015, we surveyed participants of the Harvard Flight Attendant Health Study. We compared the prevalence of their health conditions to a contemporaneous cohort in the National Health and Nutrition Examination Survey (NHANES 2013-2014) using age-weighted standardized prevalence ratios (SPRs). We also analyzed associations between job tenure and selected health outcomes, using logistic regression and adjusting for potential confounders. Results Compared to the NHANES population (n = 2729), flight attendants (n = 5366) had a higher prevalence of female reproductive cancers (SPR = 1.66, 95% CI: 1.18-2.33), cancers at all sites (SPR = 2.15, 95% CI: 1.73-2.67 among females), as well as sleep disorders, fatigue, and depression, with SPRs ranging between 1.98 and 5.57 depending on gender and the specific condition examined. In contrast, we observed a decreased prevalence of cardiac and respiratory outcomes among flight crew relative to NHANES. Health conditions that increased with longer job tenure were sleep disorders, anxiety/depression, alcohol abuse, any cancer, peripheral artery disease, sinusitis, foot surgery, infertility, and several perinatal outcomes. Conclusions We observed higher rates of specific adverse health outcomes in U.S. flight attendants compared to the general population, as well as associations between longer tenure and health conditions, which should be interpreted in light of recall bias and a cross-sectional design. Future longitudinal studies should evaluate specific exposure-disease associations among flight crew.